Exploring Culturally Sustaining Writing Pedagogy in Urban Classrooms. (November 2017) - Woodard, Rebecca; Vaughan, Andrea; Machado, Emily
We examine how culturally sustaining pedagogy that fosters linguistic and cultural pluralism might be taken up in writing instruction. Using data collected through semistructured interviews with nine urban elementary and middle school writing teachers, we document teachers' conceptualizations and enactments of culturally sustaining writing pedagogy. Findings indicate that these teachers tended to make space for explicit discussions of language, culture, and power in the writing curriculum and to problematize expressions of dominant culture, such as an emphasis on official languages. We also explore the tensions that these teachers experienced in their pedagogy while engaging in culturally sustaining methods; for example, we documented teachers' sense that writing needed to be more formal than speech and instances where their critical practices put them at odds with stakeholders in their schools. This work represents an emerging understanding of how culturally sustaining literacy pedagogy might be implemented in practice.